Discipline and Honest Character Formation through the Implementation of Electronic Traffic Law Enforcement in High School Students - Nurhanifah, Isra; Kusdarini, Eny (LPPM Undiksha, 2023)
The issue of traffic violations has been discussed by the general public for a long time. This shows a low level of discipline. This study aims to analyze the formation of disciplinary character and honesty related to the implementation of ETLE. This research is descriptive research with a qualitative approach. The subjects in this study were 2 high school Civics teachers, 2 counseling teacher, 1 high school student affairs teacher, 3 police officers, and 3 11th grade high school students. Data collection in this study was conducted by interview and documentation. Data validity checks were carried out using crosscheck techniques. While data analysis uses qualitative analysis techniques with stages: data collection, data reduction, data display and verification and confirmation of conclusions. This study resulted in the findings of the formation of Discipline Character in high school applying positive discipline because the teachers set a good example first and socialize what the benefits of school rules are. The method of forming honesty only relies on exams, reprimands and students who consult BK. Supervision related to this is also carried out when students are at school and wearing uniforms. If outside of that the school leaves it to the parents. The application of ETLE does not fully foster the character of discipline and honesty, especially in high school students. Because there are still those who violate invisible rules such as not having a SIM and ETLE can still be cheated by covering the vehicle license plate.